Prenatal Diagnosis, Associated Findings, and Postnatal Outcome in Fetuses with Double Inlet Ventricle (DIV) - Böckenhoff, Paul; Hellmund, Astrid; Gottschalk, Ingo; Berg, Christoph; Herberg, Ulrike; Geipel, Annegret; Gembruch, Ulrich (Ultraschall in der Medizin - European Journal of Ultrasound, 2022)
Purpose To assess the spectrum of associated cardiac anomalies, the intrauterine course, and postnatal outcome of fetuses with double inlet ventricle (DIV).Methods Retrospective analysis of prenatal ultrasound of 35 patients with DIV diagnosed between 2003 and 2021 in two tertiary referral centers in Germany. All fetuses underwent fetal echocardiography and a detailed anomaly scan. Postnatal outcome and follow-up data were retrieved from pediatric reports.Results 33 cases of DIV were correctly diagnosed prenatally. 24 fetuses (72.7%) had a double inlet ventricle with dominant left (DILV), 7 (21.2%) with dominant right ventricular morphology (DIRV), and 2 cases (6%) with indeterminate morphology (DIIV). 4 (16.6%) were Holmes hearts. 5 of the 7 fetuses (71.4%) with DIRV had a double outlet right ventricle (DORV). Malposition of the great arteries was present in 84.8%. Chromosomal abnormalities were absent. Termination of pregnancy was performed in 8 cases (24.2%). 24 fetuses (72.7%) were live-born. 5 (20.8%) were female and 19 (79.2%) were male. The median gestational age at birth was 38+2.5 weeks. All but one child received univentricular palliation. The median follow-up time was 5.83 years with an adjusted survival rate of 91.6% (22 of 24 live-born children). There was one case of Fontan failure at 15.7 years.Conclusion DIV remains a major cardiac malformation although both prenatal diagnostics and cardiac surgery have improved over the years. The course of pregnancy is commonly uneventful. All children need univentricular palliation. The children are slightly physically limited, develop a normal intellect, and attend school regularly.
Keywords: Echokardiografie; Fetale Kardiologie; Pädiatrische Kardiologie; Double inlet ventricle; Pränatale Diagnostik